Air Quality 2019. Preliminary Evaluation. - Minkos, Andrea; Dauert, Ute; Feigenspan, Stefan; Kessinger, Susan; Mues, Andrea (My University, 2020)
This evaluation of air quality in Germany in the year 2019 is based on preliminary data which has not yet been conclusively audited from the air monitoring networks of the federal states and the German Environment Agency (Umweltbundesamt), valid on January 2020. Due to the comprehensive quality assurance within the monitoring networks, the final data will only be available in mid-2020. The currently available data allows for a general assessment of the past year. The following pollutants were subject to consideration: particulate matter (PM10 and PM2.5), nitrogen dioxide (NO2) and ozone (O3), since, the limit and target values/WHO recommendations for the protection of human health are still exceeded for such substances.
Keywords: Luftqualität; Luftverschmutzung; Datenerhebung; Umweltschutz; Gesundheit